Innovative Distribution Company: A Total Cost Approach to Understanding Supply Chain Risk. Issue 1 (1st November 2018) - Farris, Ted; Manuj, Ila
Abstract : This case illustrates the use of the total cost of ownership concept to analyse and compare two supply chains – one international and one domestic. The case provides an opportunity to calculate economic order quantity and safety stock quantities and then combine purchase price, shipping costs, and inventory carrying costs to quantify the differences between the two supply chains.